Studies on in vitro morphogenesis and cormlet formation of Gladiolus hybridus Hort. - Bisht, Shweta (My University, 2019)
Gladiolus hybridus Hort. holds a paramount position in floriculture market because of its magnificent spikes in myriads of colours. Conventional methods of propagation are not much result yielding because of slow multiplication rate and due to pathogen attacks. In order to meet the huge demand of Gladiolus, the present study was undertaken to develop an efficient protocol for in vitro propagation of Gladiolus. The cultivar of G. hybridus was multiplied on basal MS medium containing 3 % (w/v) sucrose. The effect of auxins and cytokinins was observed on shoot proliferation of G. hybridus using various combinations and concentrations of 6-benzylaminopurine (BA) and α-naphthaleneacetic acid (NAA). Out of which maximum shoot proliferation was recorded on MS medium containing 2.5 µM each of NAA and BA. Also, the organogenesis potential from leaf segments has been demonstrated in present study using auxins such as NAA, Indole-3-acetic acid (IAA), 2,4-Dichlorophenoxyacetic acid (2,4-D). Maximum shoot organogenesis was observed on MS medium containing 5 µM 2,4-D. However, with increase in sucrose concentration shoot proliferation, rooting, cormlet formation increased significantly. Maximum shoot proliferation, rooting and cormlet formation was observed when 8 % (w/v) sucrose was used. Further, heat shock (45 ⁰C ) for 1 hour after 15 days of incubation stimulated shoot growth and rooting with maximum growth on medium containing 6 % (w/v) sucrose. Alongwith, the addition of plant growth inhibitors in basal MS medium containing 8 % (w/v) sucrose had a significant effect on growth and cormlet formation in G. hybridus. Maximum cormlet (3.86) per shoot clump were observed on medium containing 20 µM Chloro Choline Chloride.
Keywords: CCC; Diaminozide; Heat Shock; Sucrose; Inhibtors